Trauma to a Hepatoblastoma: A Case Report - Muhamad Zaki, Mohd Latiff Iqramie; Sukiman, Hamzah; Arasappan, Mohanaprakash KR; Ahmad, Ariff Iskandar (IIUM Medical Journal Malaysia, 2019)
We are reporting a case of previously undiagnosed hepatoblastoma in a healthy child, who presented acutely in a post-traumatic setting. We reported a 7-year-old boy, with no previous medical history, presented with gradual worsening abdominal pain following an episode of trivial trauma to the abdomen two weeks prior. He was anaemic at presentation, and had a distended abdomen with a tender enlarged liver. Computed tomography (CT) of the abdomen showed a grossly enlarged left lobe of the liver, within which was an organized hematoma. Serum alphafetoprotein (α-FP) was raised significantly. The liver injury was managed conservatively and the child recovered well. He is set to undergo staging scans and further workup, in anticipation of subsequent systemic therapy. Though exceedingly unlikely in older children, the diagnosis of hepatoblastoma should be entertained in those with an enlarged liver with a clinical presentation masquerading as a ‘straightforward’ liver injury.